Virtual Team: Characteristics, Internal Group Dynamics And Effectiveness - Koay, Hooi Ling (2007)
Transformation of business enterprises and stronger business competition today has prompted the emergence of virtual teams. Thus, this study attempts to understand more about virtual team effectiveness and the influences from internal group dynamics, team characteristics and task complexity. Data collected through questionnaires from 152 teams have been analysed using SPSS version 11.0. There are six hypotheses that have been tested. Among these six, only two are supported. The findings showed that team characteristics do not impact internal group dynamics or team effectiveness; while internal group dynamics correlates positively with virtual team effectiveness. Among the dimensions, it is found that team member relations correlates positively to both team performance and team member satisfaction, while team leadership is found to be correlated positively to team member satisfaction.